Effect of foliar application of plant growth regulators on incidence of insect-pests and diseases in autumn planted seed potato (Solanum tuberosum) - SINGH, AMANPREET; AULAKH, C S; KAUR, RUBALJOT; CHOUDHARY, AJAY KUMAR (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during 2019–20 and 2020–21 at Punjab Agricultural University, Ludhiana, Punjab to study the effect of foliar application of plant growth regulators on insect-pest and disease incidence in potato (Solanum tuberosum L.) under subtropical conditions. A total of 11 treatments including control were tested in a randomized complete block design (RCBD) with three replications on the potato cv. Kufri Pukhraj. The results indicated that plant growth regulators, like GA3, IBA, NAA, ethrel, jeevamrit and waste decomposer were not producing any significant effect on the incidence of aphid, jassid and whitefly population in comparison to untreated control. However, diseases such as scab and scurf did not reveal any significant differences among the plant growth regulator’s treatments except in late blight. Foliar application of gibberellic acid (200 ppm) at 45 and 60 days after sowing (DAS) significantly reduced the late blight incidence and severity in seed potato cv. Kufri Pukhraj.